Rearmament to the Rescue? New Estimates of the Impact of 'Keynesian' Policies in 1930s' Britain - Nicholas Crafts; Terence C. Mills (European Historical Economics Society (EHES), 2012)
We report estimates of the fiscal multiplier for interwar Britain based on quarterly data, time-series econometrics, and 'defense news'. We find that the government expenditure multiplier was in the range 0.5 to 0.8, much lower than previous estimates. The scope for a Keynesian solution to recession was much lower than is generally supposed. We do find that rearmament gave a substantial boost to real GDP after 1935 but this was because the private sector responded to news of massive future defense spending and does not imply that the multiplier effect of temporary public works programs would have been large.
Keywords: E62; N14; 330; defense news; multiplier; public works; rearmament